THE EFFECT OF USING ENGLISH ON PERFORMANCE IN THE OFFICE FIELD - Ernawati, Eka Yuniar; Widiastuti, Widiastuti; Harun, Yessy; Biduri, Febi Nur (Ridwan Institute, 2024)
This study examines the influence of English proficiency on performance in the office sector in the context of globalization. The ability to communicate in English is essential in an office environment that frequently interacts with business partners from different cultural backgrounds. English proficiency helps employees understand and use office technology whose instruction is in English, as well as facilitate effective cross-cultural communication. This study uses a descriptive and experimental approach, involving 36 respondents from various institutions. The results of the analysis showed that the use of English significantly improved office performance, with the average score of English use reaching 18.89 out of 25 and office performance of 28.92 out of 40. Regression analysis showed a strong positive relationship between English language use and office performance, with each increase in English language use improving office performance. In conclusion, improving English proficiency in the office environment is very effective in improving individual and organizational performance, so workplace English training programs are an important strategy to face the challenges of globalization and changes in the business world.